THE EFFECT OF STEAMED PURPLE SWEET POTATOES ON BLOOD SUGAR LEVELS IN STUDENTS OF THE NUTRITION STUDY PROGRAM AT BINA MANDIRI UNIVERSITY, GORONTALO (Journal of Health, Technology and Science (JHTS), 2026)
The rising prevalence of metabolic disorders among university students, driven by high-sugar dietary patterns, necessitates functional food interventions. Purple sweet potato (Ipomoea batatas L.) is a carbohydrate source rich in anthocyanins and fiber, potentially modulating postprandial glycemic responses. Objective: This study aims to evaluate the effect of steamed purple sweet potato consumption on blood glucose levels among students of the Nutrition Study Program at Bina Mandiri University, Gorontalo. Method: An analytical experimental study was conducted using a one-group pretest-posttest design involving 35 respondents selected through purposeful sampling. Blood glucose was measured at baseline (fasting) and 120 minutes post-intervention (100g steamed purple sweet potato). Data were analyzed using univariate and non-parametric Wilcoxon Signed Rank tests due to non-normal data distribution. Results: The mean blood glucose increased from a baseline of 122.06 mg/dL to 137.40 mg/dL post-intervention. Statistical analysis yielded a p-value < .001, indicating a significant physiological effect. Although 31.4% of respondents shifted into the pre-diabetic range, the overall mean remained within normoglycemic limits (
Keywords: Anthocyanins, Blood Glucose, Functional Food, Purple Sweet Potato, Young Adults.